Faktor Gagal Tumbuh pada Anak Berdasarkan Composite Index of Anthropometric Failure di Provinsi Sulawesi Barat: Factors of Child Growth Failure Based on the Composite Index of Anthropometric Failure in West Sulawesi Province - Latifah, Hasna Izdihar; Suyatno, Suyatno; Asna, Alfi Fairuz (Universitas Airlangga, 2024)
Background: The composite index of anthropometric failure (CIAF) provides a comprehensive measure of growth failure through various child anthropometric indicators. In regions with a high prevalence of stunting, several factors may contribute to the occurrence of growth failure in children under five years. Objectives: This study aims to analyze the factors influencing the incidence of child growth failure based on the CIAF in a province with high stunting prevalence in Indonesia. Methods: The cross-sectional study used the 2022 Indonesian Nutrition Status Survey (SSGI) data. The sample comprised children aged 0-23 months from West Sulawesi Province, totaling 1,573 children. The number of samples analyzed was 1,327 children, excluding incomplete data and outliers that were values outside a certain range and treated as missing values based on the World Health Organization (WHO). Multivariate analysis was conducted using logistic regression with a complex sample facility. Results: This study found that 24.9% of children experienced growth failure based on the CIAF. Factors associated with the incidence of growth failure based on the CIAF were older age between 12-23 months (OR=4.5; CI=2.36-8.43; p=0.000), birth weight less than 2,500 g (OR=6.85; CI=3.85-12.21; p=0.000), boys (OR=1.56; CI=1.13-2.15; p=0.000), incomplete immunization status (OR=1.8; CI=1.31-2.77; p=0.001), and poor economic status in quintile 1 (OR=2.1; CI=1.08-3.99; p=0.028). Conclusions: The risk factors for child growth failure based on the CIAF included older age, male sex, low birth weight, incomplete immunization status, and low economic status.